Perancangan Sistem Informasi Orangtua/Wali Mahasiswa Berbasis Web Pada Universitas Victory Sorong - Manuhutu, Melda Agnes; Rajagukguk, Iriene Surya (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The University of Victory Sorong realizes that there are limitations in controlling every student's development as a whole; it takes synergy with parents so that both parties can show their presence together. This parent/students’ guardian information system that was built makes it easier for parents to monitor or control the academic and non-academic activities of students of the University of Victory Sorong. Parents can help the Head of the Study Program to discipline students in improving student learning. Parents can also consult with the head of the study program regarding their child's development. In this information system, too, parents can see the student's grade as the final result of their learning efforts for one semester. This research was built using the SDLC method with a waterfall. Data were collected using documentation, observation, and interviews. This web-based parent/students’ guardian information system allows each parent/students’ guardian user to easily access the desired information. Some of the information that can be accessed is the Study Plan Card, Study Result Card, Student’s Transcript, and can consult with the Head of the Study Program through the Chatting feature. Programming language using PHP and MySQL database. The system is built in a user-friendly manner so that the system is equipped with an interface that is easy to understand and attractive.